Smart Guard: A Comprehensive Approach to Ad Click Fraud Detection - Akash Vir; Dr. Shivam Upadhyay (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Digital advertising is plagued by ad click fraud, which can result in large financial losses and skewed statistics. Current research on ad click fraud detection is summarized in this systematic review, which also assesses different methods and approaches. The review addresses difficulties, outlines the efficacy of various approaches, and makes recommendations for future lines of inquiry. Ad click fraud is the practice of creating phony clicks on internet ads, which can be done by malevolent humans, click farms, or automated bots. Click metrics are inflated by this fake activity, resulting in false performance statistics and squandered advertising budgets. Ad click fraud must be identified and stopped in order to preserve the efficacy and integrity of digital advertising campaigns. The objectives of this review are to list popular methods for detecting ad click fraud, assess how well they work in practical situations, talk about the drawbacks and restrictions of the approaches currently in use, and recommend future lines of inquiry to improve ad click fraud detection. The analysis concluded that when it comes to identifying ad click fraud, machine learning and artificial intelligence (AI) algorithms typically perform better than rule-based approaches. However, the caliber and variety of the training data determine how effective these methods are. The results emphasize how crucial it is to fight ad click fraud by utilizing sophisticated detection methods. To increase detection accuracy and lower financial losses, advertisers should spend money on AI and machine learning-based solutions. To keep up with changing fraud strategies, future research should concentrate on hybrid techniques, real-time detection, and cross-platform analysis.